FAKTOR-FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KONSENTRASI TIMBAL (Pb) DALAM DARAH PADA PEKERJA DI PERUSAHAAN ROKOK WIDO DI KABUPATEN KUDUS - Tri Anggi Huwaida; Mursid Rahardjo; Onny Setiani (Jurnal Kesehatan Masyarakat (Undip), 2016)
Lead is one of the chemicals most dangerous air pollutions in the working environment. Cigarette company is a company that could potentially lead to air pollutants contribute. So that worker in the tobacco company including people at risk of exposure to metallic lead, because the raw tobacco used contain lead. This study aims to determine risk factors for blood lead concentrations in workers in Wido Cigarette Companies at Kudus and activity of male workers who smoke in work area. This type of research is observational with cross sectional approach. The population in this study is that there is air in the working environment of the company and 86 workers in the company. Samples from this study are located at three locations of air samples with the number of respondents 46 people with simple random sampling method. The results of test fisher exact shows that there are correlation in smoking habits (p=0,029), gender (p=0,029), and nutritional status (p=0,037) with the concentration of lead in the blood as well as with smoking habits, is a risk factor with the concentration of lead in the blood (RP=2,000 ; RP >1). The conclusion of this study are there is have a relationship of smoking habits, gender, and nutritional status with the concentration of lead in the blood of workers at the cigarette company wido. Suggestions for the company applying the rules to not smoke in work area. For workers suggested using Personal Protective Equipement when working.